Impact of COVID Responses on Brand Performance - Rezkalla, Emy (AUC Knowledge Fountain, 2021)
The main objective of this study is to understand and evaluate whether COVID responses have a significant positive impact on brand performance. Accordingly, the proposed conceptual model focused on the top four COVID-19 responses: donations in cash, donations in kind, customer service, and employers/suppliers and evaluated the impact of each proposed response on brand value, brand growth, and brand ranking in 2020 versus 2019. The research question of this paper is, Do COVID responses (customer service, employers/suppliers, donations in kind, and donations in cash) have a significant positive impact on brand performance (brand value, brand growth, and brand ranking vs. 2019)? In order to answer the research question, secondary data methodology was used focusing on the responses of the top 100 brands announced in 2020 by Interbrand. The responses of each brand were analyzed based on different websites and online pages. Moreover, to validate this data, three in-depth interviews were conducted with brand managers across three companies: Nestle, Unilever, and P&G. The findings showed that none of the four COVID responses significantly and positively impacted brand value and brand ranking in 2020 versus 2019. However, customer service and donations in kind were the only responses that showed a significant positive impact on brand growth. Moreover, the brand managers agreed on the results stating that any branded activity that affects the customer directly has a significant positive impact compared to indirect and unbranded activities or services.